DISTINCTIVE FEATURES OF MUSICAL PERCEPTION - Choriyev Tohir Rozigul ogli (Web of Journals Publishing, 2024)
This article covers the issues of developing thinking skills in the performance process,based on the imagination in the art of music, as well as the creative imagination, the description of some novelty with a word or its conditional reflection (picture, musical note, etc.).
Keywords: imagination, thinking, music, attention, intuition, art, psychology, quality, feature, oberton, Polyphony, harmony, timbre, dynamics, sound, metronome, rhythmics.